A Mathematics Teacher’s Questioning Approaches for Revealing Students’ Thinking during Lesson Study - Esra Bukova Güzel, Aytuğ Özaltun Çelik, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2016)
The aim of this study is to examine the questioning approaches of a mathematics teacher participated in a lesson study model. The data of the study conducted through a qualitative case study were gathered from transcriptions of the mathematics teacher’s four-hour lessons about trigonometry and field notes of the researchers. Based on the data analysis realized by content analysis, it was seen that the teacher asked questions to reveal students’ prior knowlede, to understand their ideas and to ask them explain their corrrect responses. When examined the teacher’s questioning in terms of socio-mathematical norms, it was determined that they were insufficient for the students to have metacognitive abilities even if they were such as to encourage the students to think mathematically. It is thougt that the questions which the teacher used in the context of the lessons related to trigonometry and the evaluation of these questions will guide mathematics educators and researchers.